The Realization of Mood and Modality in the Analytical Exposition of the Undergraduate Students of Tidar University - Puspitasari, Vivanti; Warsono, Warsono; Sutopo, Djoko (English Education Journal, 2021)
Writing can be among the most enjoyable and satisfying activities to measure the ability to produce well-formed sentences. This study dealt with the realization of MOOD and Modality in the analytical exposition of the undergraduate students of Tidar University. Fifteen analytical exposition texts were analyzed to determine how the indicative MOOD, the imperative MOOD, modalization, and modulation were realized in the analytical exposition of undergraduate students of Tidar University. The type of this study is qualitative case study research. This study employed Systemic Functional Linguistics (SFL) based on Suzan Eggins (2004) as a framework since this level of structured language creates meaning that can be sought and identified. There were 511 clauses found in the fifteen analytical expositions. The result revealed several findings: (1) it was found that declarative MOOD was the most dominant of the indicative of MOOD system; (2) that the imperative MOOD type was not dominant; (3) that probability was more dominant than usuality. There were 73 clauses, or around 97% categorized as a probability, and 2 clauses or about 3% were categorized as the usuality; (4) that the obligation was dominant (14 clauses). Then, no clauses were indicated as the inclination. It was concluded that the realization could be seen from the type of indicative, imperative, modalization, and modulation that were found in the analytical exposition text of the undergraduate students of Tidar University.